MULTICRITERIA DECISION ANALYSIS IN DEFINING SERVICE LEVEL FOR CRISIS SITUATION IN OFFSHORE AIR TRANSPORT - Belmonte Möller, Eduardo; Soares Vianna, Dalessandro; de Fátima Dianin Vianna, Marcilene; Benito Mitacc Meza, Edwin (LINKSCIENCEPLACE, 2026)
To size the fleet of aircraft for offshore air transport it is necessary to consider crisis situations due to frequent climatic problems. To define the acceptable service level, the multicriteria decision method AHP (Analytic Hierarchic Process) was used in this study, resulting in 4 criteria and 5 alternatives and consistency within the allowed. The highest priority composite alternative is service level where the scenario is 1 day with 3 airports in the basin closed; Situation in which the offshore air transport operation must recover transferred flights and normalize operations within 5 days. For future work, it is suggested that this level of service defined by the AHP method be applied to the oil company for the purposes of aircraft design and process control. This application can also serve as a basis for other work in commercial air transport, road transport strikes and others.